THE INFLUENCE OF EARLY CHILDHOOD EDUCATION ON COGNITIVE AND EMOTIONAL GROWTH: A REVIEW OF EMPIRICAL FINDINGS - Buxalicha Turgunova (Bright Mind Publishing, 2025)
Early childhood is a critical period for brain development, laying the foundation for lifelong cognitive and emotional capacities. This study provides a comprehensive analysis of how early childhood education (ECE) influences young children’s mental development, focusing on cognitive and emotional outcomes. We reviewed and synthesized findings from a broad range of recent studies, including longitudinal experiments and meta-analyses, to evaluate the impacts of preschool and other ECE programs on child development. The results consistently indicate that participation in high-quality ECE significantly enhances cognitive development (e.g., language, learning abilities, and IQ) and fosters better emotional and social skills compared to children without such educational exposure. For example, meta-analytic evidence shows that preschool attendance leads to notable gains in intellectual performance and early academic skills, while also benefiting children’s social competence. Emotional development likewise improves, with ECE attendees exhibiting better emotional regulation and fewer behavioral problems. Importantly, some studies demonstrate that these early benefits translate into long-term advantages: children who attended quality preschool have higher educational attainment and lower rates of negative life outcomes (such as criminal behavior) in adulthood. The evidence underscores that investing in quality early childhood education yields significant positive effects on children’s cognitive and emotional development, with implications for education policy and lifelong wellbeing.
Keywords: Childhood, education, cognition, emotion, development, learning, intervention, psychology, success.